Learning from Berlin: How to create a dense urban area - Haberland’s Bavarian District - Locher, Michael (International Planning History Society Proceedings, 2018)
In the specialist literature, the Berlin tenement (Berliner Mietskaserne) is considered as the epitome of speculative overuse of the residential block on the eve of the Modern period. This view misses the fact that at the turn of the 19th century, several urban districts in Berlin were built for an emerging middle class that are of outstanding urban quality. The entrepreneur Georg Haberland (Berlinische Boden- Gesellschaft) developed entire neighborhoods that contributed greatly to the history of urban development at the beginning of the 20th century – a contribution seriously underestimated. In addition to the Anglo-Saxon way of suburbanization of the middle class and the French way of urbanization of the bourgeoisie within the existing town – which are commented on extensively – the urban interventions of Haberland are a little-documented third way in the history of city expansions. In this paper, first, I address the question of the urban qualities of the Bavarian District (Bayerisches Viertel), drawing on previously unpublished historical sources. And second, I propose a thesis how to place Haberland’s undervalued contribution in the wider context of Berlins planning history and beyond. Planning urban settlements from scratch is a current and crucial topic particularly in the US and in East Asia. Corresponding current projects – often designed by European planners – can be found especially in China.